Asuhan Kebidanan Pada Ibu Hamil Dengan Preeklamsi Ringan Di PMB Husnel Hayati Wilayah Kerja Puskesmas Salo Tahun 2024 - Hayati, Filza; Nislawaty, Nislawaty; Miftahurrahmi, Miftahurrahmi (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Mild pre-eclampsia is a complication in pregnancy which is characterized by hypertension. Increased systolic blood pressure of 140/90 mmHg and high levels of protein in the urine that appear at a gestational age above 20 weeks. The aim of this research is to provide midwifery care to pregnant women with mild pre-eclampsia at the PMB Husnel Hayati Working Area of ??the Salo Community Health Center starting from 10 July to 16 July 2024. This case study research was given to Mrs. S with 4 visits a week, initially the patient said he had pain in his head, his body felt weak, he had no appetite. The midwifery care provided is in the form of health education about pre-eclampsia and how to deal with it. Based on the care provided, it was found that the condition of patients with mild pre-eclampsia had reduced and improved. And it can be concluded that the care that has been provided has been carried out well. It is hoped that for health workers, this research can be a reference or material to increase insight and can be used as knowledge in counseling pregnant women regarding mild pre-eclampsia.